Case Report on Marfans Syndrome - Chetan Saoji1 , Sonal Muley2 , Sachin Daigavane3 , Tejas Sadavarte4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Marfan syndrome (MFS) is one of the most common inherited disorders of connective tissue. It is anautosomal dominant condition with a reported incidence of 1 in 3000 to 5000 individuals. There is a widerange of clinical severity associated with MFS with classic ocular, cardiovascular and musculoskeletalabnormalities, while some patients demonstrate significant involvement of the lung, skin and central nervoussystem. A 11 years old female child came to the ophthalmology OPD with chief complaints of diminution ofvision in both eyes, more in right eye since last 2 months. Patient also complains of pain in right eye sincelast 3 days. On examination patient had a tall stature, arachnodactyly with positive wrist and thumb signs,right eye had superotemporal subluxation of lens,the left eye had temporal subluxation with iridodonesis onautorefractometer patient was having high myopic reading